Determination of Young's modulus of mandibular bone using inverse analysis - Odin, Guillaume; Savoldelli, Charles; Bouchard, Pierre-Olivier; Tillier, Yannick (Medical engineering & physics, 2010)
Development of a numerical model applicable to clinical practice, and in particular oral implantology, requires knowledge of the mechanical properties of mandibular bone. The wide range of mechanical parameters found in the literature prompted us to develop an inverse analysis method that takes into account the exact geometry of each specimen tested, regardless of its shape. The Young's modulus of 3000 MPa we determined for mandibular bone using this approach is lower than the values reported in the literature. This difference can be explained by numerous experimental factors, related in particular to the bone specimens used. However, the main reason is that, unlike most previously published papers on the subject, the heterogeneity of bone led us to select a specimen size at the upper end of the scale, close to clinical reality.